Transformational Leaders in the Canadian Counselling and Psychotherapy Association: An Interview With Maria De Cicco - Morgan Kozak, Lindsay; Gray, Neal D. (Canadian Journal of Counselling and Psychotherapy, 2020)
This article, the second transcribed interview (edited for readability) in a concurrent series highlighting leaders who have been instrumental in shaping the profession in Canada, is an interview with Maria De Cicco, a prominent leader in the Canadian counselling profession. This article focuses on De Cicco’s achievements during her career and her recommendations for the future of the profession in Canada. In particular, the interview provides insight, guidance, and wisdom for ways to influence future leaders in counselling.